Ovulatory pattern and serum progesterone levels during oestrous cycle in Jamunapari goats - GOEL, A K; KHARCHE, S D (The Indian Journal of Animal Sciences, 2012)
Present study was aimed to investigate the ovarian activity in terms of ovulatory pattern (time and rate) and progesterone levels in Jamunapari. Adult cyclic goats (15) were randomly assigned to 3 treatment groups (5 in each) and laparotomized at 24, 30 and 36 h after the onset of natural oestrus to record various observations in relation to ovulatory pattern. At 24 h, group 1 (5) goats had fully developed follicles visible on ovarian surface. At 30 h (group 2), 2 of 5 goats had signs of recent rupture of ovarian follicles (corpus hemorrhagicum) and remaining follicles were in advance stage of rupture. At 36 h, group 3 (5) goats had distinct developing corpora lutea indicative of follicle rupture. The number of ova shed per doe (ovulation rate) for the ovulating doe averaged 1.45±0.20 (range 1–2). Right ovary was more functional than left ovary in terms of ovulatory points. Study revealed that ovulation in this breed occurred 30–36 h following natural oestrus i.e. towards the later part of the oestrus, considering the oestrus duration of 39 h in the breed. Based on these findings it is recommended that first mating should be allowed 10–12 h after onset of oestrus to achieve better conception rate. Levels of circulating progesterone hormone were measured in 9 adult cyclic Jamunapari goats during the period of peak oestrus activity (June - July). Progesterone levels ranged from 0.58±0.12ng/ml to 8.35±2.60ng/ml during the length of oestrous cycle. Progesterone level remained at basic level on the day of oestrus and thereafter increased gradually after ovulation. It reached to a peak level on day 14 of the cycle i.e. commencement of a new follicular wave. Information on the ovulatory pattern will permit mating at appropriate time for optimizing fertility and hormonal intervention to enhance fecundity. Study of progesterone profile will be further helpful for effective oestrus detection as well to know the reproductive status of this important breed of tropical region.